Data mining applied about state madrasah using sentiment analysis on Twitter in Indonesian perception - Mahsusi, Mahsusi; Hudaa, Syihaabul; Nuryani, Nuryani; Bahtiar, Ahmad (Institute of Advanced Engineering and Science, 2023)
Indonesian people prefer private schools with high prices, which is one of the exciting things to study. In fact, in the modern era, public schools have competed with private schools with international categories. The problem in public schools is the parent's perspective on the quality of education in public schools, especially public madrasahs. In addition, cases such as bullying and violence between schools. People on Twitter also have various perceptions of public madrasas, which are considered to have religiosity. This research uses the keywords public madrasah, quality management, and quality taken from Twitter using the Orange application. The amount of data in this research is 300 tweets from Twitter. As a result, there are both negative and positive sentiments toward public madrasas. However, the negative sentiment is higher than the positive sentiment. This means parents have more trust in private schools than in public madrasahs.